Elevating Service Quality through English Training: A Case Study of Pagaralam's Hotel and Resort Staff - Bambang Purwanto, Muhammad; Firdaus, Moch. Malik; Sutarno, Sutarno (Foreign Language Instruction Probe, 2024)
This study aims to evaluate the effectiveness of the English language training program applied to hotel and resort staff in Pagaralam, South Sumatra. English language proficiency is critical in the hospitality and tourism industry, allowing Staff to provide high-quality services to international guests. This study uses a qualitative case study approach. Data were collected through questionnaires, in-depth interviews, and observations of 50 staff participating in the three-month training program. The results showed a significant improvement in the English language skills of Staff after participating in the training program, with the average score increasing by 30%. Interactive learning methods and the use of language learning apps have proven to be effective in improving English language skills. While there are limited time constraints for Staff to participate in training, using technology helps to overcome this problem. Staff with better English skills can communicate more effectively with international guests, which positively impacts guest satisfaction and the hotel's reputation. This study concludes that structured and relevant English language training programs are very effective in improving the English language skills of hotel and resort staff in Pagaralam. Management support and investment in continuous training are essential to maintain and enhance employee competencies. This finding has significant implications for developing human resources and the attractiveness of tourist destinations in Pagaralam. Practical recommendations include increased flexibility of training schedules and collaboration with educational institutions for more comprehensive training programs.